Acellular Dermal Matrix in Plastic and Reconstructive Surgery - Mihalečko, Ján; Boháč, Martin; Danišovič, Ľuboš; Koller, Ján; Varga, Ivan; Kuniaková, Marcela (Physiological research, 2022)
Despite significant advances in medical research, plastic surgeons still face a shortage of suitable patient tissues, and soft tissue reconstruction is no exception. In recent years, there has been a rapid boom in the use of acellular dermal matrix (ADM) in reconstructive and aesthetic surgery. ADM is incorporated into the surrounding tissue and gradually replaced by the host's collagen, thus promoting and supporting the healing process and reducing the formation of scar tissue. The main goal of this article is to provide a brief review of the current literature assessing the clinical applications of ADM across a broad spectrum of applications in plastic and reconstructive surgery.
Keywords: Surgery, Plastic; Wound Healing; lidé; hojení ran; plastická chirurgie; Humans; acelulární dermis; Acellular Dermis